Cochlear hair cells: The sound-sensing machines - Goutman, Juan Diego (2015)
The sensory epithelium of the mammalian inner ear contains two types of mechanosensory cells:inner (IHC) and outer hair cells (OHC). They both transduce mechanical force generated by soundwaves into electrical signals. In their apical end, these cells possess a set of stereocilia representingthe mechanosensing organelles. IHC are responsible for detecting sounds and transmitting theacoustic information to the brain by converting graded depolarization into trains of actionpotentials in auditory nerve fibers. OHC are responsible for the active mechanical amplificationprocess that leads to the fine tuning and high sensitivity of the mammalian inner ear. This activeamplification is the consequence of the ability of OHC to alter their cell length in response tochanges in membrane potential, and is controlled by an efferent inhibitory innervation. Medialolivocochlear efferent fibers, originating in the brainstem, synapse directly at the base of OHC andrelease acetylcholine. A very special type of nicotinic receptor, assembled by a9a10 subunits,participates in this synapse. Here we review recent knowledge and the role of both afferent andefferent synapse in the inner ear.